Implementation of Visual Analytics to Enhance Budget Transparency and Accountability in Surabaya City Government - Asti Azarin; Wiwik Supratiwi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Transparency and accountability are fundamental elements of good governance, especially in regional budget management. However, the complexity of budget reports often makes them difficult for the public to understand, posing a significant challenge to financial transparency. This study aims to explore the application of visual analytics as an innovative approach to enhance budget transparency and accountability in the Surabaya City Government. Using a literature review method, this research analyzes 15 academic articles on budget transparency, accountability, and data visualization. The findings reveal that implementing technologies such as e-budgeting, interactive dashboards, and budget transparency applications significantly improves financial information accessibility. Furthermore, integrating the Regional Financial Management Information System (SIMDA) and engaging communities through Musrenbang forums strengthen budget accountability. However, challenges such as low budget literacy among the public and the need for regular data updates must be addressed. This study concludes that visual analytics not only simplifies complex financial information but also strengthens the relationship between the government and society through transparency. Future research should focus on developing a more integrated visual analytics model that includes spatial data for more effective decision-making.